Reconsidering Manifestation and Significances of Islamic Philosophy - Maulana, Abdullah Muslich Rizal; Nidzom, Muhammad Faqih; Al Faruqi, Achmad Reza Hutama; Ahmad, Choirul (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2021)
Islamic Philosophy should be observed as the worth treasure that manifested during the history of Islamic Intellectual Tradition. Quite different from the Philosophical traditions breed in Western Civilization, Islamic Philosophy affirmed its construction based on Revelation, Intuition, and demonstration. This paper will enquire several arguments reconsidering an influential position of Philosophy in Islamic Intellectual Tradition; ranged from an elaboration regarding the unity of Reason (Ratio-Intellectus), unity of existence, and the unity or relation between the Knower and the known object. Consequently, there are at least five significances of Islamic Philosophy to be studied by present-day Muslims by order: Islamic Philosophy acquired the whole competencies to seek the truth and wisdom; it is required as a systematic thought to face challenges confronted by Western Civilization; especially their destructive ideas; Islamic Philosophy also encourage mankind to find an answer an eternal question concerning the nature of their world; and finally, Islamic Philosophy counteracts the bias framework of Orientalists.